ENGLISH READING INTEREST AND COMPREHENSION OF THE STUDENTS AT A TERTIARY EDUCATION LEVEL - Ranidya Ayu Muthiah; Tri Puja Lestari; Dimas Ananto Prakoso (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
The interest in reading significantly influences students' reading performance, especially in terms of their comprehension skills. This quantitative research explores the relationship between reading interest and reading comprehension among fourth-semester English Education students at the university level in Palembang. Data were analyzed utilizing Pearson’s Product Moment correlation, based on a total sampling method of 30 participants from the academic year 2022/2023. The findings indicated negative correlations among various forms of reading interest and reading comprehension, specifically: individual interest (-0.354), situational interest (-0.319), and topic interest (-0.092). Nevertheless, the statistical significance of these correlations has not been defined, indicating a need for additional analysis. The findings reveal a noteworthy inverse relationship: As reading interest increases, reading comprehension ability tends to decrease. This unexpected result prompts an examination of the fundamental factors and possible explanations that are investigated in the research. The assessment of reading interest was conducted utilizing validated survey instruments, while comprehension was evaluated through TOEFL reading tasks. The sample size of 30 participants provides preliminary insights; however, it may restrict the broader applicability of the findings. The findings presented here hold significant implications for pedagogical approaches and curriculum development, especially in promoting a harmonious balance between stimulating interest and enhancing understanding. It is advisable to conduct additional research to elucidate these dynamics and investigate possible moderating variables.